Evaluation of kinetic parameters of immobilized penicillin G acylase subject to an inactivation and reactivation process - Romero, Oscar; Araya, Erick; Illanes, Andrés; Wilson, Lorena (Journal of molecular catalysis. B, Enzymatic, 2014)
•Immobilized PGA was inactivated by organic solvent and reactivated by two strategies.•Apparent and intrinsic kinetic parameters were calculated in three biocatalyst states.•Catalyst inactivation and reactivation significantly impacted the kinetic parameters.•Organic solvent caused conformation changes that were not restored by reactivation. Biocatalysts kinetic parameters are usually considered constant during reactor operation, which may not be the case if significant enzyme inactivation occurs and reactivation strategies are used to prolong biocatalyst lifespan. The effect of the partial inactivation and reactivation of penicillin G acylase from Escherichia coli immobilized in glyoxyl–agarose on the biocatalyst kinetic parameters was investigated. Apparent and intrinsic kinetic parameters were calculated in three biocatalyst states: native, partially inactivated and reactivated. Kinetic parameters were assessed from the initial rate of penicillin G hydrolysis at different penicillin G and phenylacetic acid (PAA) concentrations, the latter being a competitive inhibitor of the enzyme. The biocatalyst was inactivated down to 25±2% of residual activity using 70% (v/v) of dioxane and afterwards it was reactivated. Biocatalyst kinetic behavior, reflected in the Michaelis constant (KM) and inhibition constant PAA (KI), could not be restored by reactivation and conformational changes induced by the organic solvent were reflected in different intrinsic kinetic parameters of the native and reactivated biocatalyst. The significant variation of biocatalyst kinetic parameters due to its inactivation and reactivation should be considered when the enzyme reactor performance is modeled, aspect which has not been given sufficient attention up to now.